The role of alliances in creating legitimacy of sustainable technologies: A study on the field of bio-plastics. (1st July 2017) - Kishna, Maikel; Niesten, Eva; Negro, Simona; Hekkert, Marko P.
Abstract: In the transition to a more sustainable world, the development of sustainable technologies needs to be accompanied by promoting the legitimacy of the technologies. Consumers that perceive a technology as desirable and appropriate are more likely to adopt it. Organizations can collaborate to enhance the legitimacy of new technologies. While previous research has emphasized the importance of collaboration in the field of sustainability, it has not studied collaborative efforts of organizations aimed at achieving legitimacy of sustainable technologies. The contribution of this paper is therefore to analyze the role of inter-organizational alliances in creating legitimacy for a sustainable technology. The paper contributes to the literature by analyzing how alliances create three types of legitimacy: technology-sourced market legitimacy, technology-sourced social legitimacy and technology legitimacy. It focuses on the case of bio-plastics, which is emerging as a sustainable technology in the chemical industry. The analysis is based on a database containing information on 105 alliances in the field of bio-plastics over the period 1990–2013. The results show that alliances aim to promote technology-sourced market and social legitimacy by providing access to the sustainable technology of a partner, by collaboratively developing a sustainable technology, or by providing the technology of a partner with access to customers and production capacity. Alliances promote technology legitimacy by relying on positive externalities, by exercising their signaling role, and by acting as institutional entrepreneurs. The paper concludes that there are differences between alliances that create technology-sourced market and social legitimacy on the one hand, and technology legitimacy on the other hand. The first type of alliances are often bilateral alliances between for-profit companies that produce and market sustainable technologies. In contrast, alliances that stimulate technology legitimacy are multilateral alliances that operate in the pre-competitive stage of the value chain and involve not-for-profit organizations. Highlights: Organizations collaborate to enhance the legitimacy of sustainable technologies. Alliances in the bioplastics field promote market, social and technology legitimacy. Alliances promoting market and social legitimacy are bilateral for-profit alliances. Alliances promoting technology legitimacy operate in pre-competitive phase. Alliance partners act as institutional entrepreneurs to build technology legitimacy.